Pelatihan Pemasaran Online Pakan Unggas Berbahan Dasar Jerami Bawang Merah di Desa Campur Kecamatan Gondang Kabupaten Nganjuk - Sarbini, Riska Nurtantyo; Afiyah, Dyah Nurul; Supriyono, Supriyono (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2020)
Onion are horticulture commodities that having many benefits, high value and strong market outlook. Onion productivity in Nganjuk has shown high, the dust nor reached 32 tons / hectares. Along with increasing onion production in Nganjuk, the hay onion as a result side also abundant. One solution is to use it to feed alternative to poultry. It is expected that supplementation of hay onion will repair and loosening digestion poultry and nutrient feed can be used more optimal life, the growth and the production. Making poultry feed of onion hay carried out in the farmers group in the Campur village, Gondang, Nganjuk. In doing business, the farmers to compete with other companies, it took an activity was the marketing planning ranging from production to distribution. In the event itself requires a marketing strategies especially with online to face another company market products kind in the consumer market.